2018
DOI: 10.1167/iovs.17-23276
|View full text |Cite
|
Sign up to set email alerts
|

Topical Ripasudil Suppresses Retinal Ganglion Cell Death in a Mouse Model of Normal Tension Glaucoma

Abstract: METHODS. Topical administration (5 lL/day) of two different concentrations of ripasudil (0.4% and 2%) were applied to EAAC1 KO mice from 5 to 12 weeks old. Optical coherence tomography, multifocal electroretinograms, the measurement of intraocular pressure (IOP), and histopathology analyses were performed at 5, 8, and 12 weeks old. Retrograde labeling of retinal ganglion cells (RGCs), immunoblot, and immunohistochemical analyses of phosphorylated p38 mitogen-activated protein kinase (MAPK) in the retina were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 65 publications
3
24
2
Order By: Relevance
“…As already mentioned, the remaining fraction of released fasudil will most likely be eliminated via the retina. Besides their neuroprotective effects on retinal ganglion cells [19], ROCK inhibitors are under investigation for the treatment of several vitreoretinal diseases [67]. This could be very beneficial for some glaucoma patients because the prevalence of comorbid retinal disease is higher in patients with primary open-angle glaucoma (15.7%) [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned, the remaining fraction of released fasudil will most likely be eliminated via the retina. Besides their neuroprotective effects on retinal ganglion cells [19], ROCK inhibitors are under investigation for the treatment of several vitreoretinal diseases [67]. This could be very beneficial for some glaucoma patients because the prevalence of comorbid retinal disease is higher in patients with primary open-angle glaucoma (15.7%) [68].…”
Section: Discussionmentioning
confidence: 99%
“…The great advantages of this strategy are that there is no ocular surface exposure and the portion of the drug that reaches the retina may be beneficial. In fact, ROCK inhibitors have been demonstrated to have neuroprotective effects on cells of the retina [19].…”
Section: Introductionmentioning
confidence: 99%
“…Excitatory amino-acid carrier 1 (EAAC1; EAAT3) is another type of glutamate transporter and it is mainly localized to RGCs in the retina. In EAAC1 KO mouse retinas, high levels of oxidative stress markers are observed compared with wild-type mice; and in cultured RGCs from EAAC1 KO mice, susceptibility to H 2 O 2 insults is higher compared with wild-type RGCs [16,28,29]. Like GLAST KO mice, EAAC1 KO mice reproduce some aspects of sporadic, age-dependent NTG pathology and make a good mouse model of NTG [16].…”
Section: Glutamate Transporter Deficient Micementioning
confidence: 99%
“…Moreover, in human glaucoma progressive retinal degeneration occurs slowly over years, but in GLAST/EAAC1 KO mice, it starts at 3~5 weeks of age, and in GLAST heterozygous mice, it occurs more slowly (1~4 months) and the effect of a drug can be studied over a year [16,32]. Regardless of such limitations, GLAST/EAAC1 KO mice all develop NTG-like phenotypes in a consistent time-course without affecting non-RGCs in the retina [16,29] and have been useful for providing potential therapeutic targets. We demonstrated the therapeutic effects of decreasing oxidative stress in these mice and we recently reported that some widely prescribed drugs suppressed RGC death in these mice without altering IOP.…”
Section: Glutamate Transporter Deficient Micementioning
confidence: 99%
“…Mice received once-daily topical administration (5 µl/day) of PBS as the control or 2% ripasudil (Kowa Co. Ltd., Tokyo, Japan) solution in PBS. We selected this dose of ripasudil because 2% is the concentration that can be stably dissolved without precipitation at normal temperature, and 2% ripasudil was effective for RGC protection in EAAC1 KO mice 10 . 2% ripasudil or PBS was administered 3 min after ONC.…”
Section: Drug Administrationmentioning
confidence: 99%